Role of endoscopic third ventriculostomy in tuberculous meningitis with hydrocephalus - Yadav, Yad; Parihar, Vijay; Todorov, Mina; Kher, Yatin; Chaurasia, Ishwar; Pande, Sonjjay; Namdev, Hemant (Asian Journal of Neurosurgery, 2016)
Hydrocephalus is one of the commonest complications of tuberculous meningitis (TBM). It can be purely obstructive, purely communicating, or due to combinations of obstruction in addition to defective absorption of cerebrospinal fluid (CSF). Endoscopic third ventriculostomy (ETV) as an alternative to shunt procedures is an established treatment for obstructive hydrocephalus in TBM. ETV in TBM hydrocephalus can be technically very difficult, especially in acute stage of disease due to inflamed, thick, and opaque third ventricle floor. Water jet dissection can be helpful in thick and opaque ventricular floor patients, while simple blunt perforation is possible in thin and transparent floor. Lumbar peritoneal shunt is a better option for communicating hydrocephalus as compared to VP shunt or ETV. Intraoperative Doppler or neuronavigation can help in proper planning of the perforation to prevent neurovascular complications. Choroid plexus coagulation with ETV can improve success rate in infants. Results of ETV are better in good grade patients. Poor results are observed in cisternal exudates, thick and opaque third ventricle floor, acute phase, malnourished patients as compared to patients without cisternal exudates, thin and transparent third ventricle floor, chronic phase, well-nourished patients. Some of the patients, especially in poor grade, can show delayed recovery. Failure to improve after ETV can be due to blocked stoma, complex hydrocephalus, or vascular compromise. Repeated lumbar puncture can help faster normalization of the raised intracranial pressure after ETV in patients with temporary defect in CSF absorption, whereas lumbar peritoneal shunt is required in permanent defect. Repeat ETV is recommended if the stoma is blocked. ETV should be considered as treatment of choice in chronic phase of the disease in obstructive hydrocephalus.
Keywords: Cerebrospinal fluid shunt; endoscopic third ventriculostomy; hydrocephalus; neuroendoscopy; tuberculous meningitis